MENGISI POLA GAMBAR DENGAN TEKNIK KOLASE MELALUI METODE PEMBERIAN TUGAS PADA PESERTA DIDIK PAUD NEGERI PEMBINA KECAMATAN RENGAT BARAT - Widia, Endang (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
In the normal practice of collage, fine motor has not seemed to progress as they only use demonstration method in teaching. Kids less indicates a change in attitude since it tends to be passive and accept what the teacher so that the results obtained are less than the maximum, therefore, the PTK is the writer trying to dig a way to teach learning